Survivin Inhibitors as a Target Therapy for Leukemia - Ghorbani Aliabadi, Elham; Ardam, Mehdi; Shakourzadeh, Aylar; Boreiry, Rouhnaz; Esmaeili, Sogand; Bagheri, Mortaza; Emamgolizadeh, Behnam (Asian Pacific Journal of Cancer Nursing, 2025)
Leukemia is a type of cancer characterized by the accumulation of leukemic cells in the patient’s peripheral blood. Traditional therapies often fail to completely eliminate these cancer cells, especially in refractory leukemia. One major reason for this failure is apoptosis dysfunction, with anti-apoptotic proteins playing crucial roles in cancer cell survival. Among these proteins, the inhibitor of apoptosis proteins (IAPs), particularly survivin, are highly overexpressed in most cancers, including leukemia, and contribute to chemotherapy resistance. Survivin, an inhibitor of apoptosis, is typically expressed during embryonic development and in tumor cells but not in normal adult tissues. It suppresses apoptosis, thereby promoting disease progression and resistance to chemotherapy. In leukemia, survivin expression is associated with poor prognostic outcomes in both acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL). The dysregulation of apoptosis in leukemic cells is often linked to increased survivin expression, making it a promising therapeutic target. This review explores the diverse roles of survivin in mediating apoptosis, cell division, and chemoresistance in leukemia. It also discusses several survivin-targeting strategies, including ribozymes, immunotherapy, and gene therapy. Preclinical and clinical studies involving survivin inhibitors are currently underway and show promise in increasing the sensitivity of leukemic cells to standard chemotherapy treatments. These therapies, by disrupting survivin’s protective mechanisms, may lead to better treatment outcomes for leukemia patients. Understanding the complex relationship between survivin and apoptotic pathways will provide valuable insights for developing innovative therapeutic strategies against these challenging hematologic malignancies.